The politics of intermediation in transitions: Conflict and contestation over energy efficiency policy. (March 2023) - Nordt, Alexander; Raven, Rob; Malekpour, Shirin; Sharp, Darren
Abstract: This study investigates transition intermediation in energy efficiency regulation for buildings and light vehicles in Australia by using an analytical framework that draws on transition literature and the multiple streams approach (MSA) from policy studies. By focusing on Australian cases, this study examines required functions of transition intermediaries in a highly politicised context in which sustainability transitions are contested to improve an understanding of transition-oriented policy processes, including policy failures. The findings highlight the role of transition intermediaries that brought knowledge capacity into policy processes, advocated for new policy visions, and built consensus on policy proposals. The analysis suggests that the functional influence of transition intermediaries is particularly important when there is conflict among organised interests. In doing so, this study offers new insight into how transition intermediation is shaping the dynamics of energy transitions in politicised contexts.